HAMBATAN DALAM PELAKSANAAN EKSEKUSI JAMINAN FIDUSIA YANG TELAH MEMILIKI KEKUATAN EKSEKUTORIAL - NIM. A1012161205, YENI MARGARETH MARPAUNG (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACTTo support their lives, people need capital both to open bussinesses and to buy vehicle facilities. Seen this situation then many finance companies that provide funding to the public. A finance company is a bussiness entity that is specifically set up to lease, factoring, consumer financing and/or credit cards, as conducted by PT. BFI Finance Indonesia, Tbk banch pontianak which has two forms of financing, namely conventional financing and lease back financing, which can be said as a form of funding in the form of leasing and consumer financing. But to ensure the return of funds by the debtor. PT. BFI Finance Indonesia, Tbk as a creditor asks for collateral, thereby reducing the risk of loss for creditors in the even (default) by the debtor.This study aims to determine the obstacles experienced by PT. BFI Finance Indonesia Branch Pontianak in executing executions on collateral objects that already have executive power. Problem Formulation: How are the obstacles in carrying out the execution of fiduciary guarantees that have had executive power. As for the research method, it was done descriptively analytically. The method of approach is juridical empirical with primary data and secondary data analyzed qualitatively. To strengthen this research an interview was conducted.From the results of the study t was found that many debtors who then transferred the object of collateral to a third party and took the object of bail out of town which caused the creditor to incur additional costs an take up time. To minimize such an event the creditor then uses the approach to the debtor